TRANSFORMASI AKTIVITAS DAN POLA PIKIR PESERTA DIDIK MELALUI PEMBELAJARAN REFLEKTIF BERBASIS PTK DI SDN KELAYAN DALAM 7 - Maulida, Elsa; Aslamiah, Aslamiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low levels of student engagement, critical and logical thinking skills, and learning outcomes observed in a fourth-grade classroom at Kelayan Dalam 7 Public Elementary School, Banjarmasin. These issues were attributed to limited active participation and insufficient practice in analysis and logical reasoning during the learning process. The aim of this study was to describe teacher and student activity, and to enhance students’ critical and logical thinking skills as well as their learning outcomes through the implementation of the PESAN model—a combination of Problem-Based Learning (PBL), Somatic Auditory Visual Intellectual (SAVI), and Numbered Heads Together (NHT). This Classroom Action Research (CAR) was conducted over four sessions with 22 fourth-grade students. Data were collected through observation and written assessments, and analyzed using descriptive quantitative methods based on percentage scales aligned with performance indicators. The results revealed significant improvements: teacher activity increased from a score of 20 to 27 (“Very Good” category), student activity rose from 27% to 86% (“Nearly All Students Were Highly Active”), critical thinking skills improved from 32% to 86%, logical thinking from 27% to 95%, and overall learning mastery from 27% to 95%. All aspects were categorized as “Highly Skilled.” It can be concluded that the PESAN model is effective in promoting student engagement, higher-order thinking skills, and academic achievement, making it a promising innovative and collaborative learning strategy for elementary education.